Description of larvae of genera Stenelmis, Ordobrevia and Nomuraelmis (Coleoptera: Elmidae: Elminae) of Japan with their molecular taxonomy - Hayashi, Masakazu; Kamite, Yuuki; Kobayashi, Takuya; Sota, Teiji (Zootaxa, 2016)
Larvae of 10 elmid species of the genera Stenelmis, Ordobrevia and Nomuraelmis were described based on SEM observation. Of these, S. hisamatsui, S. ishiharai, S. hayashii, O. amamiensis were described for the first time, and N. amamiensis was redescribed. The morphological types of the larvae corresponded to the monophyletic groups defined by the mitochondrial COI gene tree. A new key for larvae of all species from Japan with known larva is given. The larvae of the type species of Stenelmis and Ordobrevia are also described.